1984
DOI: 10.1007/bf01857614
|View full text |Cite
|
Sign up to set email alerts
|

Physical characteristics of bone composite materials

Abstract: ABSTRACT:To study the effects of varying minerai content and various trace element.s in hone composities on its electrical hehavior and possible use in design of transducers, various physical, dielectric, piezoelectric, and eleetromechanical parameters have been measured. For electrical characterization of various such composites in the high-frequency region (1-108 MHz), variation of impedance (Z), phase angle (tan)~), and relative output voltage with frequency has been examined. Furtherfore, the Curie tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The utility of pulsed electromagnetic fields (0–300 Hz) is now successfully established for clinical use; however, their mechanism of interactions in relation to bone metabolism that influence bone healing remains to be fully understood. Earlier we have measured the impedance and phase angle of bone specimens using a vector impedance meter from 0.5 to 108 MHz and dielectric parameters at microwave frequencies 12, 14, 15. Experimenting on rabbits, it was identified that pulsating frequency of 14 MHz (modulated at ELF frequency of 16 Hz and voltage of 10 Vp‐p) is sufficient to induce a voltage of requisite magnitude to accelerate the healing process 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of pulsed electromagnetic fields (0–300 Hz) is now successfully established for clinical use; however, their mechanism of interactions in relation to bone metabolism that influence bone healing remains to be fully understood. Earlier we have measured the impedance and phase angle of bone specimens using a vector impedance meter from 0.5 to 108 MHz and dielectric parameters at microwave frequencies 12, 14, 15. Experimenting on rabbits, it was identified that pulsating frequency of 14 MHz (modulated at ELF frequency of 16 Hz and voltage of 10 Vp‐p) is sufficient to induce a voltage of requisite magnitude to accelerate the healing process 10.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier we have measured the impedance and phase angle of bone specimens using a vector impedance meter from 0.5 to 108 MHz and dielectric parameters at microwave frequencies. 12,14,15 Experimenting on rabbits, it was identified that pulsating frequency of 14 MHz (modulated at ELF frequency of 16 Hz and voltage of 10 Vp-p) is sufficient to induce a voltage of requisite magnitude to accelerate the healing process. 10 The low level field application using parallel plates ensure that the induced voltage are so small not to increase the temperature in the intervening media, particularly in the event of fluid circulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent experimentation suggests that dead bone also possesses a variety of Physical properties [15] . Therefore it seems quite pertinent to explore and correlate the presence of trace elements to the overall bone behaviour.…”
Section: Major Constituentsmentioning
confidence: 99%